223k views
5 votes
Find the general solution of the differential equation. (Use C for the constant of integration.) dy dx = 36 − 12x2 x3 − 9x + 3

User Crazylpfan
by
4.8k points

1 Answer

6 votes

Answer:


y = -4ln(x^3 - 9x + 3) + C\\

Explanation:

Given the differential equation
(dy)/(dx) = (36-12x^2)/(x^3-9x+3)\\ \\, we will use the variable separable method to solve the differential equation as shown;


(dy)/(dx) = (36-12x^2)/(x^3-9x+3)\\ \\dy = (36-12x^2)/(x^3-9x+3)dx\\ \\\\\\integrate \ both \ sides\\\\\int\limits dy = \int\limits(36-12x^2)/(x^3-9x+3)dx\\ \\\\using\ substitution\ method \ to \ solve \ RHS\\\\\int\limits(36-12x^2)/(x^3-9x+3)dx\\\\let \ u = x^3-9x+3; du/dx = 3x^2-9\\\\dx = du/3x^2-9\\\\\int\limits(36-12x^2)/(x^3-9x+3)dx\\\\ = \int\limits(36-12x^2)/(u)*(du)/(3x^2-9) \\\\= \int\limits(12(3-x^2))/(u)*(du)/(3(x^2-3))\\\\


= \int\limits(-12(x^2-3))/(u)*(du)/(3(x^2-3))\\\\= -4\int\limits (du)/(u)\\ = -4lnu + C\\= -4ln(x^3 - 9x + 3)

The differential solution becomes:


y = -4ln(x^3 - 9x + 3)
+C

User TarranJones
by
4.7k points